Effect of Informal Sector Tax Revenue on Capital Development in Lagos Metropolis - Olabisi, Jayeola; Afolabi, Adegboyega; Olagunju, Adebayo; Madariola, Folasade Ajewole (Economics and Business, 2020)
The study investigates the effect of informal sector tax proceeds on capital development in Lagos Metropolis. The study adopted Ex-post facto design to obtain secondary data, covering 20 years (2000–2019) from the Lagos State Internal Revenue Service and the Ministry of Budget and Planning. All the series were tested for normalities to determine the appropriateness of Ordinary Least Square (OLS) regression. The results of the study revealed that tax collected from the association, petty traders, and market men and women had a significant effect on capital development in Lagos Metropolis. It is evident from the monumental capital projects being executed by the government in the Metropolis. The study recommends that the government should not only create an enabling environment for the informal sector to thrive but also give all necessary support for its survival because the sector has contributed to the capital development of the Metropolis through tax revenue.